Resolution Of International Conflicts Through The United Nations: The Corfu Channel Case - Bujar Ahmedi; Shefik Shehu (European Scientific Journal, ESJ, 2016)
States have been and are still the most essential actors in international relations. The primary aim of each state is the maximal realization of its interests vis a vis other actors in the international scene. This could potentially result in a disagreement or even conflict. It is precisely the job of the international law to peacefully resolve these issues through the many mechanisms that it has under its disposition. Apart from the disagreements that could arise between/among states, such disagreement could as well arise between a state and another type of international actors e.g. in an organization or even between two or more organizations. Even in the resolution of these types of disagreements, one could apply one of the many mechanisms that are applied in the state vs. state case. When we talk of international disagreements, it is noteworthy to mention that they could be of a political nature and of a legal nature. This division is very often debated since each conflict is invariably linked with some political considerations. This is the reason why it is so difficult to define some of the criteria which would determine the very nature of the conflict and/or disagreement. There are several instruments to solve international disagreements. In the past, many of the disagreements between states were solved through war. However, since the end of the First World War, war has been considered as a forbidden means of solving disagreements between states.